2018
DOI: 10.3389/fneur.2018.00538
|View full text |Cite
|
Sign up to set email alerts
|

Middle Cerebral Artery Pulsatility Index as Predictor of Cognitive Impairment in Hypertensive Patients

Abstract: Background: Cognitive impairment is a manifestation of cerebrovascular disease regarding hypertension and other degenerative diseases which has become a global health issue due to increased life expectancy. Recently, the gold standard used for diagnosing vascular cognitive impairment (VCI) has required a combination of the neurophysiological approach and magnetic resonance imaging (MRI). The Neurosonological approach, involving measuring the pulsatility index (PI) of the middle cerebral artery (MCA) using Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…We also found a significant difference in the MCA indices between the LVAD group and the other groups. In a study investigating the PIs of MCA on cognitive impairment in hypertensive patients, higher PI values were associated with cognitive decline . Thus, it may be presumed that the lower indices of CAs and MCAs may compensate for low PSV values and establish sufficient cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found a significant difference in the MCA indices between the LVAD group and the other groups. In a study investigating the PIs of MCA on cognitive impairment in hypertensive patients, higher PI values were associated with cognitive decline . Thus, it may be presumed that the lower indices of CAs and MCAs may compensate for low PSV values and establish sufficient cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Common carotid artery (CCA), internal carotid artery (ICA), and middle cerebral artery (MCA) are critically essential components of cerebral circulation and Doppler ultrasonography has been used to evaluate the hemodynamics of these vessels. PI and resistive (RI) indices, indicators of vascular resistance, can also be calculated by obtaining PSV, EDV, and mean velocity, and can be used as an indicator of cerebral and other organ perfusion . A decrease in these indices facilitates perfusion of the organs, but their elevation indicates that perfusion of end organs becomes difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a large population-based study in Rotterdam reported that healthy older adults with lower CBF measured by MRI performed significantly worse on tasks of information processing speed, executive and global cognitive function compared to those with higher CBF [28]. In addition, cerebral artery stiffness, marked by increased PI, is also associated with cognitive impairment [29] and predicts the progression from mild cognitive impairment to dementia [30]. Combination of low BFV and high PI can result in chronic hypoperfusion, which may cause progressive loss of neuronal function [31].…”
Section: Discussionmentioning
confidence: 99%
“…it is estimated that dementia affects around 5-8% of those aged 65 years and older, and 30% of people older than 80 (1,5,11). vaD is the second most common cause of cognitive impairment in the elderly after AD, constituting 15-20% of all dementia worldwide (12,13).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Montreal Cognitive Assessment questionnaire) and brain MRi. The presence of MRi abnormalities (hypointensity in T1-weighted image and white matter lesions in T2-FLAiR) can also be used as a predictor of cognitive impairment (11). vaD clinical characteristics.…”
Section: Diagnosismentioning
confidence: 99%